Analisis Tata Ungkap Dalam Dan Luar Pada Film Animasi Pendek Death Of The Firstborn Egyptians - Citra Kemala Putri (ArtComm, 2019)
Visual Language is a knowledge that can be used to interpret various images those presented without text. Primadi Tabrani divides this Visual Language into 2 systems, the visual language system called NPM (Naturalist-Perspective-Momenopname) and another visual language system is STP (Space-Time-Plane). At this time which the technological progress has been developing very rapidly, we met many types of images, not just still images, but also moving images such as animated films, one of them is Death Of The Firstborn Egyptians directed by Nina Paley. This research uses qualitative method and uses the Visual Language Theory in analyzing the various visual towards the visuals of this film. The results of a visual study of this film revealed that there was a slice between Modern ‘Tata Ungkap Dalam’ and Traditional ‘Tata Ungkap Dalam’. Meanwhile, the researh found that Modern ‘Tata Ungkap Luar’ is dominantly use on the film. Thus it can be concluded that the RWD visual language system is not used to produce traditional images only, but also can be combined with NPM visual language system, those could enrich the result of finishing visual.